Augmented Reality Mobile Application for Autism Spectrum Disorder Rehabilitation - Taufiq, Milkhatussyafa'ah; Kurniawan Suhartono, Bryan Fernando; Sabanari, Hizkia Febriano; Musyaddad, Muhammad Naufal; Rofiq, Dzaky Ahmad (Department of Informatics Engineering, 2024)
Autism Spectrum Disorder (ASD) is a neurological disorder in which a diagnosed child may have difficulty communicating socially or may have a repeated or limited set of behaviors. Recently, ASD cases have increased dramatically. This makes scientists interested in finding various drugs or therapies that can be used for children with autism. Social behavior therapy is one of therapy that has shown effectiveness in improving fundamental symptoms of ASD. With the rapid development of technology, social behavior therapy was then expanded by utilizing some of the latest technologies that can be beneficial for children with autism. One of the therapies using the latest technology that can be utilized is making a quiz-based game by utilizing Augmented Reality (AR) to create 3D objects virtually. Spectrum Quiz is an example of an AR-based therapy game. This game is expected to improve the ability of children with autism to communicate socially. In the development of the Spectrum Quiz AR application, several tools are needed such as Adobe Illustrator, Unity, and Blender 3D.